Boss with benefits - King, Lucy, 1972- (Harlequin presents, 2024)
"CEO Adam Courtney must stay celibate or lose an acquisition that will absolve the guilt of his mother's death. No problem... Until the woman he shared an uncharacteristically impulsive encounter with walks into his Manhattan boardroom to audit his firm. Because he knows exactly how searing they are together... Being in Adam's orbit daily, unable to touch him, is torture. Only Ella Green can't cave. She won't risk her career for anyone again. Yet the more forbidden their desire, the hotter it burns and the faster they lose grip on their control..."--